Implication of Netrin-1 Gain of Expression in Canine Nodal Lymphoma - Antonin Tortereau; Nadège Milhau; Elodie Rhumy; Marie Castets; Frédérique Ponce; Patrick Mehlen; Thierry Marchal (Veterinary Sciences, 2022)
Netrin-1 is a member of the laminin superfamily, and is known to interact with specific receptors, called dependence receptors. While upon netrin-1 binding these receptors initiate positive signaling, in absence of netrin-1, these receptors trigger apoptosis. Tumor cells can avoid apoptosis by inactivating these receptors or by gaining ligand expression. The aim of the present study was to investigate the expression of netrin-1, the ligand of dependence receptors, in canine healthy lymph nodes (LN), and in lymphomas and to evaluate efficiency of a netrin-1 interfering compound in cell cultures from canine lymphoma. Thirty-two control LN and 169 lymphomas were analyzed through immunohistochemistry. Netrin-1 was expressed in the nucleoli of lymphoid and non-lymphoid cells in controls. Acquisition of a cytoplasmic expression was present in B-cell lymphomas (23.1 % in low-grade and 50.6% in high-grade) and T-cell lymphomas (50.0 % in low-grade and 78.8 % in high-grade), with a significant difference between the high- and low-grade in B-cell lymphomas. Through flow cytometry, we showed a significant increase in netrin-1 expression in either high-grade B-cell and T-cell lymphomas (19 and 5, respectively) compared with healthy LN (5), likewise an RT-qPCR analysis demonstrated a significant increase in netrin-1 expression level in 14 samples of lymphomas compared with eight samples of healthy LN. A T-cell aggressive canine lymphoma cell line and four primary canine nodal lymphomas cell cultures were treated with a netrin-1 interfering antibody. Apoptosis by measuring caspase 3 activity was significantly increased in the cell line and viability was decreased in three of the four primary cell cultures. Together, these data suggest that netrin-1 expression is increased in lymphoma, and more specifically in high-grade lymphomas, and that netrin-1 can act as a survival factor for the neoplastic cells, and so be a therapeutic target.